Incidencia social de la gripe de 1918-1919 en la ciudad de Cádiz - Herrera Rodríguez, Francisco (1996)
The main objective of this work is to study (trough documentary sources as press, municipal expedients of Beneficence and Health, capitular acts, monographs, etc) how the daily life in the city of Cádiz was altered because of the 1918-19 influenza epidemic. One of the biggest problems the municipal and sanitary authorities had to front, was the landing and lodging of the sick who arrived by sea. The placing of the lodgings was cause of several protests from the inhabitants. Also, some of the measures adopted by the Provincial Inspector of Health were disputed. There were solidary and repulse actions with the sick; it was discussed whether the 1919 Carnival had to be celebrated or not. We draw up a panoramic of the main incident happened in Cádiz because of this epidemic.